THE FIRST DISCOVERY OF AN ANGLERFISH (TELEOSTEI, LOPHIIDAE) IN THE EOCENE OF THE NORTHERN CAUCASUS - Bannikov A.F. (My University, 2004)
A new genus and species of anglerfish (Lophiidae), Eosladenia caucasica gen. et sp. nov., is described based upon a complete partly disarticulated skeleton from the Middle Eocene (Bartonian, Kuma Regional Stage) of the northern Caucasus (Gornyi Luch locality). This is the first finding of a fossil anglerfish in Russia.
Keywords: Lophiidae; anglerfish; new taxa; Middle Eocene; northern Caucasus; Russia; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен